1986
DOI: 10.1017/s0022336000060820
|View full text |Cite
|
Sign up to set email alerts
|

Ordovician Sphinctozoan Sponges from the Eastern Klamath Mountains, Northern California

Abstract: Extensive silicified faunules of Middle and Late Ordovician sphinctozoan sponges have been assembled from the northern part of the eastern Klamath Mountains in northern California. The sponges are from eugeosynclinal rocks that are the westernmost Middle Ordovician to Late Devonian rocks at that latitude in North America. Seventeen new species occur in the assemblages, including 10 porate and 7 aporate forms. New genera of porate forms are Amblysiphonelloides and Corymbospongia, and new porate species include:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…Porter (1974) reported ooids in the massive limestone member of the Facey Rock Limestone, which is probably Arenigian (Early Ordovician; Bergstrom and others, 1980), and thus is the oldest dated sedimentary rock in the Yreka terrane. Abundant dasycladacean algal debris occurs in Ashgillian limestone of member 5 of the Horseshoe Gulch unit (G. F. Elliott, in Rigby and Potter, 1986), and probable calcareous algae (R. B. Blodgett, this work) and locally common oncoids occur in Early Devonian limestone of member 3 of the Gazelle Formation. This evidence indicates that the Yreka terrane was situated in warm, tropical to subtropical latitudes from Ordovician through Devonian time, as was the western margin of North America.…”
Section: Paleolatitude Evidencementioning
confidence: 75%
See 1 more Smart Citation
“…Porter (1974) reported ooids in the massive limestone member of the Facey Rock Limestone, which is probably Arenigian (Early Ordovician; Bergstrom and others, 1980), and thus is the oldest dated sedimentary rock in the Yreka terrane. Abundant dasycladacean algal debris occurs in Ashgillian limestone of member 5 of the Horseshoe Gulch unit (G. F. Elliott, in Rigby and Potter, 1986), and probable calcareous algae (R. B. Blodgett, this work) and locally common oncoids occur in Early Devonian limestone of member 3 of the Gazelle Formation. This evidence indicates that the Yreka terrane was situated in warm, tropical to subtropical latitudes from Ordovician through Devonian time, as was the western margin of North America.…”
Section: Paleolatitude Evidencementioning
confidence: 75%
“…Hotz (1977), Lindsley-Griffin and Griffin (1983), and Potter and others (1977) provided maps and descriptions of the major rock units in the terrane; other relevant work includes that of Cashman (1980), Lindsley-Griffin (1977, Lindsley-Griffin and Fisher (1989), Lindsley-Griffin and , Potter ( , 1982, Rigby and Potter (1986), Savage (1976bSavage ( , 1977, Wallin (1988Wallin ( , 1989, and Wallin and others (1988). We have summarized schematically in Figure 2 the descriptions, inferred ages, and contact relations of the units pertinent to this report, and comment below only on some points that need elaboration or emphasis.…”
Section: Yreka Terranementioning
confidence: 99%
“…Although the presence of autochthonous dasycladacean algae would indicate very shallow water (Flügel 2004), the rare, fragmented occurrences of Dasyporella and Vermiporella are probably reworked and transported downslope from shallower habitats where they are abundant and intact (Bian and Zhou 1990;Li et al 2015). Corymbospongia is known from deeper subtidal settings elsewhere such as the Ordovician of the eastern Klamath Mountains in northern California (Rigby and Potter 1986). In contrast to the silicified holotype from California, Corymbospongia at Wu'ai is embedded in massive limestone.…”
Section: Discussionmentioning
confidence: 99%
“…Ordovician sphinctozoans are also rare elsewhere, which may be a consequence of their narrow-niche breadth and a poor geological record of their preferred habitat. Ordovician sphinctozoans seem to have preferred warm and low-energy deeper subtidal environments (Rigby and Potter 1986;Rigby et al 2008a, b;Senowbari-Daryan and Rigby 2011), rather than the more readily preserved shallow subtidal zone. Some authors suggested that the limited occurrence of Ordovician sphinctozoans was related to the subduction of most island-arc terranes (Carrera and Rigby 2004), which was their preferred habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of hypercalcified sponges proposed by Finks and Rigby (2004) is used for description of sponges in this paper. Morphological terms conform to the terminology presented in Kaesler (2004) and illustrated by Rigby and Potter (1986), of which the following terms are of special importance in the description and study of Hajarispongia: 1) cribribulla-inward facing, blisterlike sieve at the inner end of an exaulos; 2) cribripore-small pores in sievelike cribribulla; and, 3) exaulosspoutlike tube in sponge wall.…”
Section: Introductionmentioning
confidence: 94%